Water management of a solar-powered irrigation system: a case study in Vale do Cavaco in Benguela, Angola - Mossande, Anaclides Rogério (Revista de Ciências Agro-Ambientais, 2025)
The use of clean and renewable energy sources, such as solar PV, can help mitigate the effects on climate change, reduce pollution, energy dependence on fossil fuels, help restore degraded land and boost agricultural production. The main objective of this research work is to evaluate the uniformity of the discharge of the emitters for different irrigation conditions. The experiment was carried out in Vale do Cavaco, Benguela province, Angola, located at 12º 36’ south latitude and 13º 53’ east longitude, with an altitude of 26 m above mean sea level. The soil of the experimental area is of the clayey type that corresponds to the Chromic Luvisol according to the World Soil Resource Reference Base. With regard to solar energy, it has usable power on a large scale with availability of up to 7 hours solar peak, being one of the highest globally, the weather data were obtained through the Weather and Windy application, which coincides with those obtained on the website PVGIS (January 2015). The treatment applied to the soil was leaf composting in the entire plot of the experimental area. The coefficient of uniformity was based on the selection of 16 emitters evenly distributed within the subunit on four sides: the closest, the farthest and those located at 1/3 and 2/3 of the length of the tertiary tube, in which four emitters were selected following the same criteria. The measurement of the emitters was carried out with the help of plastic funnels to improve the accuracy of water collection. This was measured with 10 mL samples and precision timers. During the measurement, all emitters in operation were observed to determine the existence of obstructions. The value of the flow uniformity coefficient was determined from the mean value of the four emitters with the lowest flow rate and the mean flow rate of all emitters in the subunit. The irrigation system was highly uniform in its different modes of operation, and the moisture stored in the soil profile during the rainy season affected irrigation.